Chromosomal Stability and its Effect on Morphology of Wheat-Thinopyrum elongatum Disomic Addition Lines - Khatiwada, Homnath; Pant, Deepak Raj; Joshi, Giri Prasad (Journal of Institute of Science and Technology, 2025)
The introduction of chromosomes from wild relatives is of great importance as it helps in wheat improvement programs by introducing many useful traits like those related to stress tolerance that lead to increased yield, thereby contributing to food security and safety. In this regard, seven Chinese spring wheat addition lines disomic to different chromosomes from Thinopyrum elongatum were compared with the normal Chinese spring in order to study the chromosome stability and effect of disomic addition lines on spike characteristics. All the wheat lines were obtained from NBRP-Wheat Japan. Chromosome numbers were reconfirmed by counting from the mitotic metaphase spread of root tip cells, and spike and seed characteristics were measured from fully matured spikes. All the disomic addition lines showed a stable number of chromosomes (i.e., 44). The spike lengths of disomic addition lines were significantly different (P<0.05) from that of Chinese Spring (control). The seed set was higher in CS+2E’’ disomic addition lines, while the seed size and seed weight of 100 seeds were lower than that of Chinese Spring.